PROBLEM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DALAM RANGKA PERCEPATAN PENSERTIPIKATAN HAK ATAS TANAH DI KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - KHOIRUDDIN KHOIRUDDIN (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Syafruddin Kalo2. Muhd Yamin3. Edy Ikhsan One of the main objectives of the enactment of Law No. 5/1960 on UUPA is to realize the legal certainty of land title for all Indonesian people. In order to realize the legal certainty of the rights over the land in the society, PTSL (Fully Systematical Land Registration) is established to hasten the process to issue land title certificates to the society in general and citizens in Kepulauan Meranti Regency in particular. This research employs the normative juridical research method. This research is descriptive analytical. The results of the research find out The number of land registered before PTSL program is implemented in 2017 was 10%) of total area of 5,795.24 hectare i.e. 579.24 hectare or 8,560 parcel of land in Kepulauan Meranti Regency. The internal obstacles are the lack of coordination among institutions, experts in land mapping and measurement. The solution to tackle the obstacle is by conducting meetings among institutions.Keywords: PTSL, Hasten Land Registration, Kepulauan Meranti Regency